Effects of cold water immersion on lower extremity joint biomechanics during running - Fukuchi, C. A.; da Rocha, E. S.; Stefanyshyn, D. J. (Journal of Sports Sciences, 2015)
The purpose of this study was to identify the influence of cryotherapy on lower extremity running biomechanics. Twenty-six healthy male volunteers were randomised into two intervention groups: cold water (cold water at ~11°C) or tepid water (tepid water at ~26°C). They were required to run at 4.0 ± 0.2 m/s before and after they underwent water immersion for 20 min. Differences between pre- and post-intervention were used to compare the influence of water intervention during running. Peak joint angles, peak joint moments, peak ground reaction forces (GRF) and contact time (CT) were calculated using three-dimensional gait analysis. Independent t-tests were applied with a significant alpha level set at 0.05. Decreased peak propulsive and vertical GRF, decreased plantarflexion moments, increased hip flexion angle and longer CT were observed following cold water immersion. Although cold water immersion (cryotherapy) affected the running movement, none of the alterations have been related to running biomechanical patterns associated with injuries. Therefore, our results indicated that cold water immersion appears safe prior to running activities.